P5PPRA IN THE IMPLEMENTATION OF THE MERDEKA CURRICULUM - Aan Fadia Annur; Muhammad Maskur Musa; Syafa’atul Khusna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The project to strengthen the profile of Pancasila students and rahmatan lil alamin students (P5PPRA) is a new thing in the implementation of an independent curriculum. One of the madrasahs that has implemented P5PPRA is MI Walisongo Kranji 01 Kedungwuni Pekalongan. This madrasah became a piloting madrasah and has implemented P5PPRA at all levels, from grade 1 to 6. This study aims to explore the implementation of P5PPRA in this MI along with its supporting and inhibiting factors. This type of research is a field research. The approach taken in this research uses a qualitative approach. The data sources in this study are the madrasah head, teachers and students. The data were collected using interview, observation and documentation techniques. The result of this study is that the implementation of P5PPRA in MI Walisongo Kranji 01 Kedungwuni Pekalongan is carried out through the planning stage, implementation and evaluation. Supporting factors in the implementation of P5PPRA are the relatively young age of teachers, high motivation from students and good cooperation between teachers and students. While the inhibiting factors for the implementation of P5PPRA are the teaching mindset of teachers, inadequate facilities and infrastructure and teachers' low understanding of the concept of P5PPRA. This research contributes to P5PPRA activities that can be carried out by other schools at the primary level.